Abdominal emergencies after liver transplantation: Presentation and surgical management. Issue 11 (21st September 2017) - Cesaretti, Manuela; Dioguardi Burgio, Marco; Zarzavadjian Le Bian, Alban
ABSTRACT: With an increasing number of liver transplantation (LT) and an enhanced overall survival, LT recipients are more likely to be admitted in emergency departments of general hospitals. Yet, in LT recipients, common but also benign symptoms may reveal a LT‐related (or not) severe condition. To improve management of LT recipients by emergency physicians and general surgeons and potentially improve long‐term outcomes, a clinical review was performed. Overall, CT scan and blood tests should be systematically performed. Immunosuppressive side effects should be excluded using blood tests. LT‐related complications are more likely to occur during the first three months after LT, including mainly bile leak, arterial aneurysm, and pseudoaneurysm. Patients should be referred in emergency to tertiary centers. Non‐LT‐related complications and common abdominal conditions may also be diagnosed in LT recipients. Except in case of diffuse peritonitis or in hemodynamically unstable patients when surgical procedure should be performed, most conditions should be reassessed regarding the immunosuppressive treatment and the adhesive abdominal cavity.